2002
DOI: 10.1093/carcin/23.1.67
|View full text |Cite
|
Sign up to set email alerts
|

The FANCG Fanconi anemia protein interacts with CYP2E1: possible role in protection against oxidative DNA damage

Abstract: Fanconi anemia (FA) is a genetic disorder that leads to aplastic anemia and birth defects and predisposes to cancer. FA cells exhibit characteristic hypersensitivity to DNA cross-linking agents such as mitomycin C (MMC), and FANCG is one of six known FA gene products. By immunocytochemical analysis of transfected cells, we discovered that although FANCG localized to both the nucleus and cytoplasm, there was an increase in cells with predominantly cytoplasmic staining after treatment with MMC. Concurrently, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 34 publications
3
68
0
1
Order By: Relevance
“…The FA proteins are thus believed to play important roles in the maintenance of hematopoiesis. Consistent with the observations that cells derived from FA patients are intolerant of oxidative stress, it has been reported that FA proteins, particularly the complementation group C (FANCC) protein, play a crucial role in oxidative-stress signaling in a variety of cell types including hematopoietic cells (Kruyt et al, 1998;Cumming et al, 2001;Hadjur et al, 2001;Futaki et al, 2002;Park et al, 2004;Saadatzadeh et al, 2004;Pagano et al, 2005). More recently, cytokine hypersensitivity of FA hematopoietic cells to apoptotic cues has also been proposed as a major factor in the pathogenesis of BM failure in three FA mouse models…”
Section: Introductionmentioning
confidence: 65%
“…The FA proteins are thus believed to play important roles in the maintenance of hematopoiesis. Consistent with the observations that cells derived from FA patients are intolerant of oxidative stress, it has been reported that FA proteins, particularly the complementation group C (FANCC) protein, play a crucial role in oxidative-stress signaling in a variety of cell types including hematopoietic cells (Kruyt et al, 1998;Cumming et al, 2001;Hadjur et al, 2001;Futaki et al, 2002;Park et al, 2004;Saadatzadeh et al, 2004;Pagano et al, 2005). More recently, cytokine hypersensitivity of FA hematopoietic cells to apoptotic cues has also been proposed as a major factor in the pathogenesis of BM failure in three FA mouse models…”
Section: Introductionmentioning
confidence: 65%
“…39 In addition, FANCG interacts with cytochrome P450 2E1, which is associated with the production of reactive oxygen intermediates, and the mitochondrial antioxidant enzyme peroxiredoxin-3. 40,41 Finally, we recently reported that FANCD2 associated with FOXO3a, a master regulator of oxidative stress response. 42 Although these observations point to the involvement of FA proteins in oxidative stress response, the molecular mechanism by which FA proteins function to modulate oxidative stress response has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by the Fanconi gene C (FANCC) has been shown to associate with redox-related activities, namely, NADPH cytochrome P450 reductase (Kruyt et al 1998) and glutathione S-transferase (Cumming et al 2001). A recent study has provided evidence that the FANCG protein interacts with cytochrome P450 2E1 protein, an activity also known to be involved in redox biotransformation of xenobiotics (Futaki et al 2002). Previous indirect evidence for an abnormal regulation of xenobiotic biotransformation in FA cells was provided by Joenje and Oostra (1986), who reported excess sensitivity of FA cells to cyclophosphamide without S-9 metabolic activation (Madle 1981).…”
Section: Prooxidant State In Fa Phenotypementioning
confidence: 99%